The Bad Guys in superbad - Blabey, Aaron (New York : Scholastic Inc., 2018)
The Bad Guys have strangely acquired superpowers! But their powers might be, well, defective. They can only do things like blow their own pants off in public. Not exactly what you'd call hero-caliber skills. Defective or not, the Bad Guys have a job to do. With Dr. Marmalade ready to destroy the world, Mr. Wolf, Mr. Snake, Mr. Piranha, and Mr. Shark finally have their chance to be (super)heroes! And this time, they may just get some help.
2.7
3-6
530L
Keywords: Animals -- Comic books, strips, etc. -- Fiction; Rescues -- Comic books, strips, etc; Heroes -- Comic books, strips, etc. -- Fiction; Animals -- Juvenile fiction; Rescues -- Juvenile fiction; Heroes -- Juvenile fiction; Humorous comics; Graphic novels; Graphic novels